The Paris Agreement: Consequences for the EU and Carbon Markets? - Andresen, Steinar (2016)
Most observers argue that this agreement is a step in the right direction. However, we do not know how effective it will be in terms of reducing emissions. We therefore discuss its potential effectiveness regarding EU climate policies and carbon markets. We argue that the Paris Agreement may have a positive effect but uncertainties abound.